Use and Consumption of Social Networks in the Academic and Social Environment of Administration Students at the “Universidad Colegio Mayor De Cundinamarca, Bogotá”. - Guerrero, Lugo Manuel Barbosa; Rozo, Jairo Jamith Palacios (Journal of Ecohumanism, 2024)
Social networks have become a fundamental part of everyday life, influencing multiple areas, especially in the academic and social spheres. Its use has grown exponentially, regardless of age, transforming the way people interact and access information. The objective of this study is to analyze the impact of the use and consumption of social networks on the students of Administration at the Universidad Colegio Mayor de Cundinamarca, evaluating the level of control that this exerts on them and its influence on academic and social dynamics. Using a mixed-approach methodology, combining surveys and interviews with statistical data analysis, we examine the relationship between time of use, technology dependence and the effects on academic performance and interpersonal relationships. The results show that, although social networks facilitate communication and access to academic information, their inappropriate use can generate distractions, affect productivity and contribute to the depersonalization of interactions. This study concludes that it is essential to encourage a conscious and regulated use of social networks, promoting strategies to balance their impact on the academic and social development of students. In addition, it highlights the importance of generating institutional policies that help guide young people in building responsible digital habits.